Buddhism between Asia and Europe: The Concept of Mindfulness through a Historical Lens - Tamara DITRICH (Asian Studies, 2016)
Since the beginning of the twentieth century mindfulness has been positioned at the core of modern Buddhism and viewed by many modern interpreters as an essential component of Buddhist doctrine and practices. More recently, the practice of mindfulness has become rapidly popularised, radically secularised and removed from its Buddhist context, employed mainly as a therapeutic tool or applied for the enhancement of well-being. This paper examines the concept of mindfulness using an historical lens, aiming to identify some of the main parameters and consequent implications involved in the changes and developments of this Buddhist contemplative method—from its early beginnings over 2,500 years ago to the present day. Special attention is given to the historical developments in the colonial period, when various Buddhist traditions encountered the main European discourses of the time, resulting in the birth of modern Buddhism. In this period, particularly in Burma, meditation was positioned at the centre of Buddhist teachings and thus provided the grounds and conditions for the subsequent popularisation and secularisation of mindfulness in the late twentieth century. Through an examination of the concept of mindfulness through history, the paper explores whether a critical awareness of historical facts provides a better understanding of the current ubiquity of mindfulness practices worldwide. In addition, mindfulness has recently become an object of scientific research and, hence, it is important to investigate it in different contexts and discourses throughout history, and understand the implications of various definitions, interpretations and applications of mindfulness for the development of modern research approaches and methodologies.